Integrating Classical, Modern, and Contemporary Islamic Educational Thought: The Role of Islamic Legal Values in Shaping National Law - Nur Hakima Akhirani Nasution; Afrizal; Mira Yanti Lubis; Sutan Botung Hasibuan; Riki Saputra; Saifullah Saifullah; Anuar Ahmad (Attractive : Innovative Education Journal, 2026)
The discourse on Islamic educational thought has evolved through three distinct epistemic phases—classical, modern, and contemporary—each contributing unique perspectives on the relationship between knowledge, morality, and legal reasoning. This article examines how these three traditions of Islamic educational thought can be integrated into a coherent framework for shaping national law in Indonesia, a Muslim-majority nation founded on the pluralistic ideology of Pancasila. Employing a qualitative research methodology with a normative legal and educational-philosophical approach, this study analyzes primary and secondary sources, including classical Islamic legal texts, modern reformist writings, contemporary Indonesian scholarly works, and national legislation. The findings reveal that classical Islamic educational thought provides foundational epistemic authority through textual (bayānī) reasoning; modern thought contributes rational (ta‘līlī) methodologies and institutional reforms; while contemporary thought offers contextual (maqāṣidī) hermeneutics and transformative pedagogies. The integration of these three traditions manifests in Indonesian legal instruments such as the Compilation of Islamic Law (KHI), Law No. 18/2019 on Pesantren, and the Merdeka Curriculum, which reflect Islamic legal values including justice (‘adl), consultation (syūrā), and public interest (maṣlaḥah). Furthermore, this integration demonstrates substantive compatibility with Pancasila, particularly the First Principle (Belief in the One Supreme God) and the Fourth Principle (Democracy guided by consultative wisdom). This study contributes to the theoretical discourse on Islamic legal education reform and offers practical insights for harmonizing religious values with national legal development in pluralistic societiesv.